1997
DOI: 10.1002/j.1939-4640.1997.tb02437.x
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor (α and β) Expression in the Excurrent Ducts of the Adult Male Rat Reproductive Tract

REX A. HESS,
DANIEL H. GIST,
DAVID BUNICK
et al.

Abstract: The understanding of estrogen's function in the male reproductive tract is limited, and estrogen receptor (ER) localization in the reproductive tract of the adult male rat has not been described. In the present study, ERα was localized by immunohistochemistry using ER21 antibody, which recognizes only ERα. Strongest immunoreactivity was seen in epithelia of ductuli efferentes and the initial segment of the epididymis. Nuclei of both ciliated and nonciliated cells were positive. The epithelium of the rete testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…As known, estrogens have an important role in maintenance of some aspects of epididymal physiology [ 14 ]. The expression of ERs has been widely documented in the epididymis of several species (mice, rats, dogs, cats, and monkeys) [ 32 , 35 , 36 , 46 , 58 ] with a common observation of the presence of ER-alpha in the efferent ductules that not only provide to the reabsorption of more than 90% of the rete testis fluid but concentrate sperm for epididymal storage [ 59 ]. In addition, the very wide GPER expression in the epididymis of pigs [ 28 , 60 ], rats [ 30 ], sheep [ 61 ] and in humans’ ductuli efferents and proximal epididymis [ 29 ] suggests its involvement in sperm maturation, protection, and storage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As known, estrogens have an important role in maintenance of some aspects of epididymal physiology [ 14 ]. The expression of ERs has been widely documented in the epididymis of several species (mice, rats, dogs, cats, and monkeys) [ 32 , 35 , 36 , 46 , 58 ] with a common observation of the presence of ER-alpha in the efferent ductules that not only provide to the reabsorption of more than 90% of the rete testis fluid but concentrate sperm for epididymal storage [ 59 ]. In addition, the very wide GPER expression in the epididymis of pigs [ 28 , 60 ], rats [ 30 ], sheep [ 61 ] and in humans’ ductuli efferents and proximal epididymis [ 29 ] suggests its involvement in sperm maturation, protection, and storage.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in dogs, limited studies have shown its presence in testes with and without tumors [ 31 ], and no data are available for dog epididymis. On the other hand, the pattern of classic estrogen receptors’ protein abundance was studied in the male reproductive tracts of some animal species including dogs [ 32 , 33 , 34 ], humans [ 35 ], and rodents [ 26 , 36 ], evidencing some differences in their distribution. In our opinion, knowledge is limited regarding both the tissue-specific distribution and coexistence of these three estrogen receptors in normal and cryptorchid conditions in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Similar research on females concluded that production of sterility was due to the precise targeting of the kisspeptin neurons during a critical period of neonatal development, which permanently suppressed pituitary gonadotrophins LH and FSH ( 57 ). Regardless of testicular effects, estrogen also has direct effects on the reproductive tract, particularly targeting the efferent ductules, where ESR has the highest expression and is co-expressed with AR ( 440 , 441 ). Disrupting the ESR1 or AR pathway in the male reproductive tract can permanently disrupt luminal physiology, leading to back-pressure atrophy of the testis, independent of the HPG axis ( 132 , 133 , 139 , 440 ).…”
Section: Methods Of Sterilizationmentioning
confidence: 99%
“…Besides androgens, other steroids, notably oestrogens, play a key role in male reproductive physiology; they influence the hypothalamic-pituitary-testis axis and spermatogenesis by acting on Sertoli, Leydig and germ cell functions (Hess et al, 1997;O'Donnell et al, 2001). Oestrogens are involved in spermatogonial stem cell division (Miura et al, 1999).…”
Section: Introductionmentioning
confidence: 99%